2013
DOI: 10.2340/00015555-1476
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histopathological Features of Folliculotropic Mycosis Fungoides: A Norwegian Patient Series

Abstract: Folliculotropic mycosis fungoides is a variant of cutaneous T-cell lymphoma with distinct clinicopathological features. We describe here the clinical presentation, pathology findings and treatment outcome in 15 Norwegian patients. All patients were diagnosed between 1997 and 2010 at Oslo University Hospital. A spectrum of skin lesions, both typical and atypical, such as leonine facies, acneiform lesions, psoriasiform plaques, purulent ulcerations and cystic milia-like lesions for mycosis fungoides, were seen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
14

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 18 publications
2
50
1
14
Order By: Relevance
“…Some atypical forms of MF, such as folliculotropic MF, bullous MF and granulomatous MF, have been reported to show more aggressive behaviour than classical MF (8)(9)(10)(11)(12). In our case, the haematoma-like mass was associated with CD30* large-cell transformation.…”
Section: Discussionmentioning
confidence: 66%
“…Some atypical forms of MF, such as folliculotropic MF, bullous MF and granulomatous MF, have been reported to show more aggressive behaviour than classical MF (8)(9)(10)(11)(12). In our case, the haematoma-like mass was associated with CD30* large-cell transformation.…”
Section: Discussionmentioning
confidence: 66%
“…Da Pruritus ein Hauptsymptom der FMF ist, zeigte einer unserer Patienten dauerhafte generalisierte Exkoriationen [ 12 ] . Akneiforme FMF-Läsionen sind histologisch durch eine neoplastische Infi ltration der Zystenwand gekennzeichnet.…”
Section: Geschlecht/alter Stadium * Verwendete Behandlungen Effektivsunclassified
“…The pathology includes perivascular and periadnexal dermal T-cell infiltrates, with hyperchromatic and cerebriform nuclei, and sparing of the epidermis (folliculotropism instead of epidermotropism). Most cases show follicular mucinosis and cells are positive for cell surface markers in flow cytometry CD3+, CD4+, and CD8- [32,33]. Regarding treatment, it has recently been reported that psoralen plus UVA (systemic/bath) is effective [33], as well as combination with bexarotene or interferon [34,35].…”
Section: Cutaneous T-cell Lymphomamentioning
confidence: 96%